2014
DOI: 10.1002/mus.24209
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional area reference values of nerves in the lower extremities using ultrasonography

Abstract: The lower extremity nerve CSA values obtained in this study may provide normal reference values for the Asian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
70
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 32 publications
(69 reference statements)
17
70
2
Order By: Relevance
“…In our study, mean value of ΔSx–Asx was 4.83±2.83 mm 2 and ΔSx–Asx of 1.7 mm 2 as cutoff value yielded a sensitivity of 83.3% and a specificity 96.7%. In agreement with our findings, previous studies reported 3.2 mm 2 and 4.9 mm 2 upper limit of side-to-side difference, respectively; but data were obtained from healthy subjects and the validity or diagnostic accuracy were not assessed [69]. …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In our study, mean value of ΔSx–Asx was 4.83±2.83 mm 2 and ΔSx–Asx of 1.7 mm 2 as cutoff value yielded a sensitivity of 83.3% and a specificity 96.7%. In agreement with our findings, previous studies reported 3.2 mm 2 and 4.9 mm 2 upper limit of side-to-side difference, respectively; but data were obtained from healthy subjects and the validity or diagnostic accuracy were not assessed [69]. …”
Section: Discussionsupporting
confidence: 91%
“…Some previous studies described upper limit value of the side-to-side difference [6922]; in addition, one study showed no significant correlation with subjects' baseline demographic factors including age, height, weight, and BMI in CF nerve [9]. Therefore, these absolute values could be a useful reference for detection of nerve pathology in people with different age and body index [691022]. In our study, mean value of ΔSx–Asx was 4.83±2.83 mm 2 and ΔSx–Asx of 1.7 mm 2 as cutoff value yielded a sensitivity of 83.3% and a specificity 96.7%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations